ANALISIS STRATEGI KOMUNIKASI MAHKAMAH KONSTITUSI DALAM MENANGGAPI KRITIK PUBLIK TERHADAP PUTUSAN BATAS USIA CALON PRESIDEN DAN KEPALA DAERAH - Indrasta Alif Yudistira; Wijayanto Wijayanto (Journal of Politic and Government Studies, 2026)
This study analyzes the communication strategy of the Constitutional Court of the Republic of Indonesia in responding to public criticism of Decision Number 90/PUU-XXI/2023 regarding the minimum age requirement for presidential and regional head candidates, a decision that triggered widespread national controversy and a dominance of negative sentiment across digital media concerning the Court's independence and institutional integrity. This study employs a qualitative approach with a case study design, with data collected through in-depth interviews and documentation study, analyzed using three complementary theoretical frameworks: Lasswell's Communication Model to examine the structure of institutional communication, Coombs' Situational Crisis Communication Theory (SCCT) to classify crisis response strategies, and Public Trust Theory to assess the impact of communication on public trust. The findings indicate that the Court's communication strategy is dominated by a diminish strategy in the form of justification, emphasizing the constitutional legitimacy of the decision without acknowledging wrongdoing, complemented by rebuild elements through the formation of the Constitutional Court Honorary Council (MKMK) and subsequent corrective rulings. This strategy proved effective in procedurally restoring general public trust, reflected in a trust score increase from 50.4 percent in December 2023 to 71.2 percent in March 2024, yet insufficient in building substantive legitimacy among civil society and critical, educated groups, whose skepticism persisted as fundamental ethical questions remained unanswered. This duality of effectiveness constitutes the study's main finding, with a theoretical contribution suggesting that for judicial institutions, institutional action itself constitutes the most decisive communicative message.